(untitled) (Faridpur Medical College Journal, 2025)
Placental polyp is a rare postpartum complication resulting from retained placental tissue that forms a polypoidal mass in the uterus after delivery or abortion. This case report describes a 30 year old woman who developed secondary postpartum hemorrhage (PPH) due to a necrosed myomatous polyp. She initially presented with excessive postpartum bleeding following a home delivery. Despite undergoing uterine evacuation and multiple blood transfusions, she continued to experience irregular per vaginal bleeding, leading to readmission. Ultrasonography revealed a mixed echogenic structure in the uterine cavity. On examination, a necrotic mass was found protruding through the cervical os, leading to emergency laparotomy. Due to severe adhesion and persistent hemorrhage, a total hysterectomy was performed. Histopathological analysis confirmed the diagnosis of a placental polyp. This case highlights the importance of considering placental polyp in patients with persistent postpartum bleeding and emphasizes the need for early diagnosis and intervention in managing secondary PPH to prevent life-threatening complications. Faridpur Med. Coll. J. 2025;20(2):53-56